Роль активних форм кисню в підвищенні термостабільності антиоксидантних ферментів коренів пшениці після теплового загартування - Карпець, Ю.В.; Колупаєв, Ю.Є.; Мусатенко, Л.І. (Видавничий дім "Академперіодика" НАН України, 2008)
The influence of short-term high-temperature hardening (42 ºС, 1 min) of wheat plantlets on the activity and the thermostability of catalase and peroxidase has been studied. Hardening caused an increase of the activity and the thermostability of both enzymes. The pretreatments of plantlets with the inhibitor of protein biosynthesis, cycloheximide, or with the antioxidant, ionol, substantially levelled the stated changes. The conclusion about the role of the reactive oxygen species as signal intermediates and the induced protein biosynthesis in changes of the activity and the thermostability of antioxidative enzymes of plantlets after the heat hardening has been made.